Optimalisasi Peran Audit Syariah dalam Meningkatkan Akuntabilitas Sosial Lembaga Keuangan Syariah: Pendekatan Konsptual dan Berbasis Capaian - Nurvadillah, Nurvadillah; Firayanti, Firayanti; Mashyuri, Mashyuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the optimization of the role of Sharia audit in enhancing the social accountability of Islamic financial institutions through a conceptual and achievement-based approach. The development of Islamic financial institutions requires an audit mechanism that not only ensures Sharia compliance but also evaluates the effectiveness of social responsibility programs aligned with maqashid Sharia principles. Sharia audit plays a crucial role in strengthening transparency, accountability, and public trust by assessing both financial and social performance. This research employs a qualitative conceptual approach supported by an analysis of relevant literature to explore the integration of Sharia audit, Islamic Social Reporting, and governance frameworks. The findings indicate that strengthening auditor competence, standardizing Sharia audit practices, and utilizing digital-based audit systems significantly enhance the measurement and disclosure of social performance. An achievement-based audit approach enables Islamic financial institutions to demonstrate tangible social impact and sustainability. Consequently, Sharia audit functions as a strategic instrument in balancing economic objectives and social responsibility within the Islamic finance ecosystem.